Pengaruh Persepsi Kemanfaatan, Kemudahan Penggunaan, Kenyamanan Dan Risiko Terhadap Minat Nasabah Menggunakan E-Banking Bank Syariah Indonesia Di Masa Pandemi Covid-19 (Studi Pada Pengguna E-BankingDi Kota Malang) - Nur Aidah; Nur Diana; Junaidi Junaidi (El-Aswaq, 2020)
This study aims to determine the effect of perceptions of benefit, convenience, comfort, and risk on customer interest in using e-banking Bank Syariah Indonesia during the covid-19 pandemic in malang city. Samples were taken using purposive sampling method. The method used in this study uses quantitative methods using multiple linier regression analysis technique and hypothesis testing with SPSS. The result of data analysis show that the perception of benefit convenience, comfort, and risk simultaneously affects customer interest in using Bank Syariah Indonesia e-banking during the covid-19 pandemic. Partially, perceptions of convenience and comfort affect customer interest in using Bank Syariah Indonesia during the covid-19 pandemic, while perceptions of benefit and risk have no effect on customer interest in using e-banking Bank Syariah Indonesia during the covid-19 pandemic in the city of malang.